Potential of herbal formulas and bioactive metabolites in treating atherosclerosis: targeted modulation of macrophage polarization - Liu, Shixin; Jing, Jinpeng; Zhang, Yunsha; Sun, Junchao; Zhu, Chaojun (Frontiers in Pharmacology, 2025)
Macrophage polarization plays a pivotal role in the pathogenesis and plaque stability of atherosclerosis (AS). In response to microenvironmental cues, macrophages differentiate into pro-inflammatory M1 or anti-inflammatory M2 phenotypes, which respectively exacerbate or mitigate inflammatory responses and influence plaque progression. Emerging evidence highlights the therapeutic potential of targeting macrophage polarization through signaling pathways such as Toll-like receptor 4 (TLR4)/nuclear factor-kappa B (NF-κB), peroxisome proliferator-activated receptor γ (PPAR-γ), Janus kinase (JAK)-signal transducer and activator of transcription (STAT), phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) pathway, and mitogen-activated protein kinase (MAPK) pathway. Bioactive metabolites derived from traditional Chinese medicine (TCM)—including ginsenosides (e.g., Rb1, Rg3), berberine (BBR), curcumin (CUR), and tanshinone IIA (Tan IIA)—as well as herbal formulas like Bu Yang Huan Wu Decoction (BYHW) and Zhuyu Pill (ZYP), have demonstrated efficacy in promoting M2 polarization and suppressing M1 phenotypes, thereby attenuating AS. This review critically synthesizes the current body of evidence, with a primary focus on preclinical studies (in vitro and in vivo), which comprehensively synthesizes evidence on the targeted modulation of AS-associated macrophage polarization by bioactive metabolites and herbal formulas, with a unique emphasis on the role of TCM as a multi-target regulator of macrophage plasticity. This approach provides novel perspectives for the prevention and treatment of AS.